‘Unhappy Lovers’? Difficulties of Spiritual Transition and the Case of Environmentalist ‘New Animism’ - Ondřej Beran; Olli Lagerspetz (Religions)
In this paper, we reflect on difficulties connected with transitioning from one spiritual tradition to another. We consider Western New Animism, sometimes proposed as a remedy to the exploitative and anthropocentric values typical of Western Modernity. New Animism hopes to provide a framework for resilient, pro-environmental attitudes and practices. Referring to Wittgenstein’s reflections on religion, magic and culture, as well as the work of Peter Winch, we argue that the possibility of embracing another form of spirituality depends on one’s ability to see a ‘depth’ in it. However, a conversion always has an element of the unpredictable, as we never know in advance what awaits us on the other side. This creates problems for purely pragmatically oriented suggestions to adopt an animist worldview.